Effects of overlap length on the strength of bolted, bonded and hybrid single lap joints with different adherend materials and thicknesses. Issue 20 (18th October 2019) - Kadioglu, F.; Demiral, M.; El Zaroug, M.
Abstract: This study evaluates the effects of the overlap length and different adherend materials with different thicknesses on the mechanical performance of the bolted (BJ), adhesively bonded (ADJ) and hybrid joints (HJ) subjected to quasi-static axial tensile loading. The three different joints were fabricated and tested according to 36 different variances, including two kinds of adherend materials (AL6061 and Al7075 with different yield strength, tensile strength and ductility values), three adherend thicknesses (2 mm, 4 mm and 6 mm) and two overlap lengths (25 mm and 45 mm). Numerical models were implemented and developed using the commercial software Abaqus/Explicit. The adhesive layer (AF163-2K) was simulated by using cohesive interface elements with traction-separation response. Ductile/shear damage models were used to simulate the failure behavior of the adherends and the bolt material. To interpret the strength of various joints, failure behavior for each configuration is analyzed widely.